2019
DOI: 10.2174/1570179416666190312150046
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Novel Fluorine Compounds Substituted-4-thiazolidinones Derived from Rhodanine Drug as Highly Bioactive Probes

Abstract: <P>Aim and Objective: It is known that rhodanine drug has various biocidal activities. The aim of this work was to improve the structure of rhodanine drug via alkylation at N, S, and O- centers in addition to the introduction of fluorine atoms. The new fluorinated modified rhodanines 2-16 were evaluated as enzymatic probes for cellobiase activity produced by fungi and as CDK2 inhibitors of tumor cells. </P><P> Materials and Methods: Novel fluorine substituted N-alkyl, S-alkyl and amino-rhodan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…Some new 4-thiazolidinones and bis-compounds have been synthesized and derived from condensation of 4-aminoantipyrine with aromatic aldehyde followed by cycloaddition of thioglycolic acid in a non-polar solvent. Fluorine substituted thiazolidin-4-one moiety bearing antipyrine nucleus enhanced the enzymatic effects of the bacteria, which agreed with last results published [19] [20] [21].…”
Section: Resultssupporting
confidence: 91%
“…Some new 4-thiazolidinones and bis-compounds have been synthesized and derived from condensation of 4-aminoantipyrine with aromatic aldehyde followed by cycloaddition of thioglycolic acid in a non-polar solvent. Fluorine substituted thiazolidin-4-one moiety bearing antipyrine nucleus enhanced the enzymatic effects of the bacteria, which agreed with last results published [19] [20] [21].…”
Section: Resultssupporting
confidence: 91%
“…Studies showed that the growth of the tumor can be effectively inhibited by MIF inhibitors and the inhibitory effect can be significantly enhanced by adding fluorine atoms (Dziedzic et al 2015 ). Similarly, other fluorinated compounds also exhibited stronger inhibitory effects than non-fluorinated compounds for distinct tumor cells, such as fluorinated green tea polyphenols, fluorinated largazole, fluorinated 4-thiazolidinone, fluorinated griseofulvin, fluorinated l -threonine, fluorinated aminophosphonite, and fluorinated docetaxel (Zhang et al 2019a ) (Stadlbauer et al 2018 ) (Makki et al 2019 ; Olgun 2019 ; Paguigan et al 2017 ; Sudileti et al 2019 ; Tang et al 2016 ). These results indicated that the incorporation of fluorine-substituted fragments into the inhibitor is an effective means to enhance the therapeutic effect of tumors.…”
Section: Applications Of Fluorinated Compoundsmentioning
confidence: 99%
“…Benzylpenicillin (antibacterial) and Imidil (antifungal) were used as the standard antibiotics and used DMSO as solvent and control, under the concentration of 100 μg/ml of each compound. The growth inhibition calculated in each case concerning control [28] [29]. Nutrient agar medium used for growing bacteria while Czapeck's medium used for growing fungi and incubated lasted for 48 h at 37˚C for bacteria and seven days at 28˚C for fungi.…”
Section: The Antimicrobial Evaluationmentioning
confidence: 99%